2018
DOI: 10.1007/s10880-018-9547-x
|View full text |Cite
|
Sign up to set email alerts
|

Does Hope Matter? Associations Among Self-Reported Hope, Anxiety, and Health-Related Quality of Life in Children and Adolescents with Cancer

Abstract: This study aimed to examine the direct and indirect effects of hope on health-related quality of life (HRQoL) via anxiety of children/adolescents with cancer. We proposed to test if the mediation model was moderated by the child/adolescent's treatment status. The participants were 211 children/adolescents diagnosed with cancer, divided into two clinical groups according to treatment status: 97 patients on-treatment and 114 off-treatment. Self-reported questionnaires measured the youths' hope, anxiety, and HRQo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 58 publications
0
24
1
5
Order By: Relevance
“…The number of participants in the studies ranged from 37 to 224, and most used convenience sampling. Hope was measured using the Children's Hope Scale [13][14][15] Index [16]. The PedsQLTM 4.0 Generic Core Scale, PedsQL 3.0 Cancer Module, Miami Pediatric Quality of Life Questionnaire, and the short version of the DISABKIDS Chronic Generic Measure self-report questionnaire were used to measure quality of life.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of participants in the studies ranged from 37 to 224, and most used convenience sampling. Hope was measured using the Children's Hope Scale [13][14][15] Index [16]. The PedsQLTM 4.0 Generic Core Scale, PedsQL 3.0 Cancer Module, Miami Pediatric Quality of Life Questionnaire, and the short version of the DISABKIDS Chronic Generic Measure self-report questionnaire were used to measure quality of life.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…All five studies reported a positive correlation between hope and quality of life, meaning that people with higher levels of hope had a better quality of life. One study reported that hope had significant direct and indirect effects on quality of life [16], while another study reported that anxiety mediated the relationship between hope and quality of life [13]. One study also reported that hope was a mediator in the relationship between quality of life and adaptive behavior [15].…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, success during treatments and interventions should build hope in children. Decreasing anxiety (Martins et al, 2018) before treatments and procedures can help with success in treatments and procedures. This can be done in a multitude of ways including use of pharmacologic and nonpharmacologic agents (Nunns et al, 2018).…”
Section: Nursing Implicationsmentioning
confidence: 99%
“…Sposito et al (2015) found that keeping alive the hope of cure was an essential coping mechanism in their exploration of persons undergoing chemotherapy for cancer. Hope has been related to better health outcomes in several chronic diseases such as asthma (Berg, Rapoff, Snyder, & Belmont, 2007), irritable bowel disease (Nicholas et al, 2007), cancer (Herth, 2000;Hinds et al, 1999;Martins et al, 2018;Sposito et al, 2015), renal and liver transplant (Maikranz, Steele, Dreyer, Stratman, & Bovaird, 2007), sickle cell disease (Lewis & Kliewer, 1996), and juvenile rheumatoid arthritis (Connelly, 2005;Sällfors, Fasth, & Hallberg, 2002). Specifically, it has been documented in previous studies that children with higher hope with chronic illnesses, have better treatment adherence including inhalers with asthma (Berg et al, 2007), renal and liver transplant medications (Maikranz et al, 2007), and irritable bowel disease treatment (Nicholas et al, 2007).…”
Section: Introductionmentioning
confidence: 99%